SIÇANLARDA SİSPLATİN İLE OLUŞTURULAN TESTİS HASARINA KARŞI EPİGALLOKATEŞİN-3-GALLAT'IN BAZI PROTEİN SİNYAL YOLAKLARINA ETKİSİ - ÖZDEMİR, İLKAY (Fırat Üniveristesi, 2023)
Son yıllarda aldığımız gıdalardan, yediğimiz besinlerden, yaşam şartlarımızdan, hava kirliliğinden ve kalıtsal olaylardan ötürü kansere yakalanma riskimiz giderek artmaktadır. Dünya genelinde bakıldığında kanser en yaygın ikinci hastalık olarak görülmekte ve yapılan çalışmalara göre önümüzde ki 10 yıl içinde ilk sıralarda yer alacağı da düşünülmektedir. Anti-inflamatuar, antimutajenik ve antioksidatif etkisi olduğu bilinen epigallokateşin-3-gallat (EGCG)'ın çilek, üzüm ve nar benzeri taneli meyvelerde ve ceviz gibi yiyeceklerde bulunan bir polifenol türevi olduğu belirlenmiştir. Kanser tedavisinde kullanılan ilaçlardan biri olan sisplatinin doku da kalıcı hasarlara yol açtığı bilinmektedir. Sisplatinin neden olduğu testis toksisitesine karşı antikanserojen ve antioksidan etkilere sahip polifenolik bir kateşin olan EGCG'nin koruyucu etkisinin belirlenmesi amaçlanmıştır. Bu çalışmada, 28 adet erkek sıçan 4 gruba ayrılarak yapılmıştır ve deneyler 28 gün devam etmiştir. Sisplatin ve EGCG tek doz olarak intraperitonal (ip) şekilde sıçanlara verilmiştir. TNF-?, Bcl-2, NF-?B ve Bax proteinlerin ekspresyonları western blotlama yöntemiyle belirlenerek testis dokusunun histopatolojik incelemesi yapılmıştır ve bulgular istatiksel olarak değerlendirilmiştir. Sonuç olarak testis dokuda tedavi özelliği olan EGCG'nin uygulandığı sıçan gruplarında, malondialdehit (MDA)'in seviyesinde azalış, katalaz (CAT)'ın aktivitesinde ve glutatyon (GSH)'un seviyesinde ise artış gözlenmiştir. EGCG ile tedavi edilen grupta (EGCG+Cis) enflamasyon göstergesi olan proteinlerin ekspresyon seviyelerinin, sisplatin (Cis) grubuna oranla önemli ölçüde azaldığı görülmüştür. Histopatolojik çalışmada sisplatinin uygulandığı grupta belirgin olarak testislerde hasar oluştuğu ve EGCG verilen tedavi grubunda ise azalma olduğu gözlenmiştir. Bu bulgular, sisplatin ile oluşturulan testis toksisitesinde, EGCG ile yapılan tedavinin antienflamatuar etki gösterdiği ve testis toksisitesini büyük oranda önleyebildiğini göstermektedir.

In recent years, risk of contracting cancer has been increasing day by day due to the nutritions we take, foods we eat, heredity, our condition of life and air pollution. Around the world, when it is looking, cancer is seen as the second most common disease and according to the studies doing, this diease thought that it will take first place in pole position in the next ten years. It has been determined that epigallocatechin-3 gallate (EGCG) which is known to have anti-inflammatory, antimutagenic and antioxidative effects is a derivation from polyphenol and it is found in stone fruit such as strawberries, grapes and pomegrahates; and in foods such as waltnut. It is determined that EGCG has a protective effect also on testicular issue and prevents growth of tumar formation in cancer cells. It has been known in studies that cisplatin, one of the drugs used in cancer treatment, couses permanent damage to the tissue. It was aimed to determine the protective effect of EGCG, a polyphenolic catechin with anticarcinogenic and antioxidant structure, against testicular toxicity caused by cisplatin, against tissue damage and testicular toxicity inuced by cisplatin. In this study, 28 male rats were divided into four groups and the experiments continued 28 days. Cisplatin and EGCG were given to rats intraperitoneally as a only dose. Expressions of, TNF-?, Bcl-2, NF-?B and Bax proteins were determined by western blotting and histopathological examination of testicular tissue was performed and the findings were evaluated statistically. As a result, a decrease in malondialdehyde (MDA) levels and an increase in catalase (CAT) activity and glutathione (GSH) levels were observed in rat groups in which EGCG, which has therapeutic properties in testicular tissue, was administered. It was observed that the expression levels of proteins that are indicators of inflammation in the group treated with EGCG (EGCG+Cis) were significantly reduced compared to the cisplatin (Cis) group. In the histopathological study, it was observed that there was significant damage to the testicles in the cisplatin-administered group and a decrease in the EGCG-administered treatment group. According to these findings, in testicular toxicity induced by cisplatin, treatment with EGCG has an anti-inflammatory effect and can prevent testicular toxicity to a large extent.
Effect of epigallocatechin-3 gallate on some protein signaling pathways against cisplatin-induced testicular damage in rats
Keywords: Biyoteknoloji; Biyoloji; Genetik